Love relationships and identity development in selected Asian American chick lit - Mazloomian, Maryam; Raihanah M. M.,; Shahizah Ismail@Hamdan, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper examines the connections between love relationships and self-identity development of two selected heroines belonging to two different minority groups in America -- the Indian and the Chinese. For this purpose, two chick lit novels, Tanuja Desai Hidier’s Born Confused (2002) and Kim Wong Keltner’s The Dim Sum of All Things (2004) are selected. By employing a conceptualised framework, influenced by Bronfenbrenner’s ecological systems of development and Berry’s model of acculturation, the present paper focuses on the ethnic community and the American society in which the individuals are set. Comparing the love relationships as represented within both novels indicates how the connections and interactions between the selected heroines’ and their self-identity development influence the ways they acculturate with the mainstream culture as well as retain their own ethnicity. Although the theme of love has always dominated the chick lit genre, the present paper aims to fuse the notion of romance with culture and diaspora. This investigation shows how the selected theme is significant in the identity development process of the female protagonists. Therefore, this paper explicates the different aspects of a love relationship with regards to the heroines’ interactions with the ethnic community and the American society. The findings show different cultural orientations between choosing a love target who belongs to the same minority group of the selected heroine and that of the mainstream Caucasian society. Furthermore, the findings indicate the influential role of a love relationship on identity development as represented within the selected novels.